2001
DOI: 10.1021/bi015543f
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Structure of the G-Protein-Coupled Receptor Rhodopsin Including the Putative G-Protein Binding Site in Unactivated and Activated Forms

Abstract: Activation of G-protein coupled receptors (GPCR) is not yet understood. A recent structure showed most of rhodopsin in the ground (not activated) state of the GPCR, but the cytoplasmic face, which couples to the G protein in signal transduction, was not well-defined. We have determined an experimental three-dimensional structure for rhodopsin in the unactivated state, which shows good agreement with the crystal structure in the transmembrane domain. This new structure defines the cytoplasmic face of rhodopsin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
79
1
1

Year Published

2003
2003
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 47 publications
3
79
1
1
Order By: Relevance
“…Therefore, it is reasonable to presume that they would also be favorable within the setting of the NHE1 protein. Indeed, a number of studies have demonstrated strong correspondence between structures of peptides or protein segments obtained in membrane mimetic solvents to structures obtained by solution state NMR in micelles or to entire membrane proteins determined by x-ray crystallography (11)(12)(13). Most interestingly, we find that CD 3 OH:CDCl 3 :H 2 O provides a well defined peptide structure, whereas the peptide in Me 2 SO appears much less structured.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Therefore, it is reasonable to presume that they would also be favorable within the setting of the NHE1 protein. Indeed, a number of studies have demonstrated strong correspondence between structures of peptides or protein segments obtained in membrane mimetic solvents to structures obtained by solution state NMR in micelles or to entire membrane proteins determined by x-ray crystallography (11)(12)(13). Most interestingly, we find that CD 3 OH:CDCl 3 :H 2 O provides a well defined peptide structure, whereas the peptide in Me 2 SO appears much less structured.…”
Section: Discussionsupporting
confidence: 50%
“…This provides insight into structured regions, in our case, without fixing the segment as a whole into a single conformation. The use of solution conditions having a low dielectric constant to mimic a membrane environment has become quite common for structural studies of transmembrane proteins or peptides and has provided structures of isolated protein segments consistent with their structures in the full protein (11)(12)(13). Our study demonstrates that whereas TM IV is structured, only a 4 -6-residue stretch of the segment is helical.…”
mentioning
confidence: 51%
“…using x-ray crystallography [36]. Moreover, a set of experimental distance constraints for darkadapted rhodopsin has been compiled in [57]. Thus, dark-adapted rhodopsin is an appropriate test case for our numerical experiments.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…For our second set of tests, 87 structures were generated using the procedure outlined in [17] and a set of 27 distance constraints, D 1 , obtained from [57]. This procedure resulted in structures that have no experimental distance penalty, i.e., P E = 0, where P E is as defined in (3.3), for each of the 87 structures with respect to D 1 .…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation